THE IMPACT OF CLOUD ACCOUNTING ON ENHANCING THE ACCURACY AND TRANSPARENCY OF FINANCIAL REPORTS-AN APPLIED STUDY ON A SAMPLE OF IRAQI BANKS - Murtadha Basil Ganim; Zaid Abdul Salam Muhammad (Scholars Digest Publishing, 2025)
This study aims to identify the impact of cloud accounting, through its dimensions (ease of data access, data security and protection, savings, and financial efficiency), on enhancing the accuracy and transparency of financial reports in Iraqi banks. A descriptive and analytical approach was used to achieve the study's objectives. A questionnaire was designed and distributed to a random sample of (168) employees working in the financial and accounting departments at Rafidain Bank and Rashid Bank at their headquarters in Baghdad Governorate. The resulting data was then analyzed using SPSS. The results showed strong support from the sample members for the study's axes, as it was found that the dimensions of cloud accounting represented by (ease of access to data, security and data protection, savings and financial efficiency) positively affect enhancing the accuracy and transparency of financial reports in Iraqi banks. This indicates that the adoption of cloud accounting by Iraqi banks is an important step towards development in the banking sector. In addition, its adoption helps in enhancing investor confidence, improving the administrative decision-making process, and increasing operational efficiency in these banks.
Keywords: Cloud accounting, ease of data access, security and data protection, financial savings and efficiency, accuracy and transparency of financial reports.